Contribuições da legislação urbanística e edilícia na prevenção, controle e mitigação das inundações urbanas: o caso de cidades de porte médio da Bacia Tietê-Jacaré (UGRHI – 13) - Laura, Sérgio Andrés Apaza (Universidade Federal de São Carlos, 2024)
The increase in losses caused by floods in the state of São Paulo in recent years is worrying. Many recent cases report material damage and even human losses due to intense storms that cause floods in the bottom of urban valleys. In this sense, the objective of this work is to carry out an analysis of the applicable urban and building legislation for flood prevention, control and mitigation in medium-sized cities in the state of São Paulo (from 100,000 to 500,000 inhabitants). The cities that comprise the case study of this work are Araraquara, Bauru, Jaú, and São Carlos. These cities are located in the four municipalities, which have the same name and which, in the the area of the Tietê-Jacaré River Basin (UGRHI-13), have the largest population. In this context of urban and building legislation, this work researched the legal clauses linked to the subject, established in the Master Plans, in the Buildings Codes, and in the Land Use and Occupation Laws, in the mentioned municipalities. Based on this delimitation, an analysis was developed on two levels: the first one identified and systematized the legal provisions of each city, and the second one established a comparative analysis between the four cities, looking for similarities and specificities. In this way, it is intended that this investigation on urban legislation and its contributions to the prevention, control and mitigation of urban floods in the four cities that make up the case study, has contributed to future revisions of legislation applicable to monitoring, measures and procedures, as well as in future interventions.
Contributions of urban planning and building legislation in the prevention, control and mitigation of urban flooding: the case of medium-sized cities in the Tietê-Jacaré Basin (UGRHI – 13)
Keywords: Inundações urbanas; Legislação urbanística; Bacia Tietê-Jacaré (UGRHI-13); Urban floods; Urban legislation; Tietê-Jacaré river basin (UGHRI-13); CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::DRENAGEM URBANA DE AGUAS PLUVIAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::LEGISLACAO URBANA E REGIONAL